Extraction of Pyocyanin Pigment from Pseudomonas aeruginosa and its Effect on the Growth of some Human Pathogenic Bacteria. - زينب, أسمهان; سلامي, مايا (Latakia University Journal -Biological Sciences Series, 2020)
Antibiotic-resistant bacteria are a common widespread health problem. Chemical drugs used in the manufacture of commercial antibiotics have negative side effects on human health. This is the reason why we try to look for new, effective materials against various antibiotic-resistant bacteria. Pyocyanin were extracted from liquid bacterial cultures of Pseudomonas aeruginosa using the organic solvent chloroform. Pseudomonas aeruginosa cultures were isolated from samples obtained from the laboratories of Tishreen University Hospital. Its effect on microbial growth was studied using disk diffusion test. the results showed that pyocyanin has an antibiotic effect on gram-positive bacteria (Streptococcus pneumonia, Staphylococcus aureus ) and gram-negative bacteria(Escherichia coli ) with growth inhibition zones of (25 mm), (28 mm), (10 mm) respectively.